2009
DOI: 10.1088/0004-637x/704/2/898
|View full text |Cite
|
Sign up to set email alerts
|

The Star Formation History and Extended Structure of the Hercules Milky Way Satellite

Abstract: We present imaging of the recently discovered Hercules Milky Way satellite and its surrounding regions to study its structure, star formation history and to thoroughly search for signs of disruption. We robustly determine the distance, luminosity, size and morphology of Hercules utilizing a bootstrap approach to characterize our uncertainties. We derive a distance to Hercules of 133 ± 6 kpc via a comparison to empirical and theoretical isochrones. As previous studies have found, Hercules is very elongated, wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
167
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(181 citation statements)
references
References 55 publications
11
167
3
Order By: Relevance
“…Sand et al 2009;Musella et al 2012), as recently confirmed by Brown et al (2012) with Hubble Space Telescope (HST) data. Martin et al (2008) measured the galaxy half-light radius (r h = 8.6 ), and Sand et al (2009) estimated the tidal radius (r t = 35.25 ). Hercules appears highly elongated with an ellipticity e 0.65 (Coleman et al 2007;Martin et al 2008) and shows indications of a possible tidal disruption (e.g.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Sand et al 2009;Musella et al 2012), as recently confirmed by Brown et al (2012) with Hubble Space Telescope (HST) data. Martin et al (2008) measured the galaxy half-light radius (r h = 8.6 ), and Sand et al (2009) estimated the tidal radius (r t = 35.25 ). Hercules appears highly elongated with an ellipticity e 0.65 (Coleman et al 2007;Martin et al 2008) and shows indications of a possible tidal disruption (e.g.…”
Section: Introductionsupporting
confidence: 53%
“…Since the earliest groundbased observations, it was recognized that the galaxy CMD resembles that of an old and metal-poor GGC (t 10 ± 2 Gyr and Z ∼ 10 −4 , see e.g. Sand et al 2009;Musella et al 2012), as recently confirmed by Brown et al (2012) with Hubble Space Telescope (HST) data. Martin et al (2008) measured the galaxy half-light radius (r h = 8.6 ), and Sand et al (2009) estimated the tidal radius (r t = 35.25 ).…”
Section: Introductionmentioning
confidence: 95%
“…To compute the late-time SFR we follow (Orban et al 2008) assuming that about 1% of the total stellar mass content of dSph is produced in the latest Gyr. We use SFR results reported in (Dolphin et al 2005) (Carina and Fornax), (deBoer et al 2012) (Sculptor), and (Sand et al 2009) (Hercules). For a very recent comprehensive study of SFR of dwarf galaxies in the Local Group, see (Weisz et al 2014).…”
Section: Cosmic-ray Sourcesmentioning
confidence: 99%
“…In the second, we instead consider the magnetic field to be induced only by the SF in the latest Gyr and assume (following (Orban et al 2008)) that 1% of the total stellar mass content of the dSph is produced in such range of time. We consider the same SFR estimates reported in Section 4.2 (i.e., (Dolphin et al 2005) for Carina and Fornax, (deBoer et al 2012) for Sculptor, and (Sand et al 2009) for BootesII, Hercules, and Segue2).…”
Section: Sf Rmentioning
confidence: 99%
“…At M V = −6.6 mag, Hercules is one of the brighter UFDs. Hercules is a typical, metal-poor, old stellar population (>12 Gyr) that has experienced little to no star formation in the past 12 Gyr (Sand et al 2009;Musella et al 2012; but cf. Brown et al 2012).…”
Section: Introductionmentioning
confidence: 99%